Brown adipose tissue activity and melanoma outcomes: A retrospective analysis of 135 patients - Toivanen, Pauli (My University, 2025)
Brown adipose tissue (BAT) may play a role in cancer progression. Previous studies have shown that BAT activity is higher in patients with cancer, and that BAT volume is a predictor of tumour recurrence and mortality; however, data on melanoma is limited. Here, we re-analyzed the fluorodeoxyglucose positron emission tomography – computed tomography (FDG-PET-CT) images of 135 cutaneous melanoma patients treated at Turku University Hospital between the years 2012 to 2021 to assess the association of BAT and melanoma progression, patient survival and patient weight. We applied a three-stage universal threshold definition of BAT at predetermined standardized uptake values (SUVs) at different thresholds due to the retrospective nature of our study. Clinical data were collected manually from the electronic patient records of Turku University hospital. In our cohort the prevalence of active BAT was considerable, suggesting that melanoma ranks among cancers associated with high BAT activity. We assessed whether BAT status predicted disease-free survival among patients with localized disease and melanoma mortality among patients with metastatic disease. However, due to the limited number of BAT positive patients, we were unable to test the prognostic significance of BAT volume. Furthermore, we investigated the associations of BAT status and volume on disease stage at diagnosis, BRAF mutations and patient weight. Our study demonstrates the need for further research on BAT and cancer, ideally utilizing a multicenter approach to achieve a cohort with more BAT positive patients.
Keywords: Ruskea, rasva, melanooma, ennuste